Comparative study of creep and fatigue crack growth in Poly (Vinyl chloride) pipe (Baghdad Science Journal, 2012)
The Rate theory of crack growth in PVC pipe has been studied for creep and fatigue crack propagation. Rate theory function parameters, (RTFP), were estimated theoretically from exponential function parameters, (EFP), to experimental data of crack velocity versus stress intensity factor ,(V-K) diagram, to creep crack propagation . Also (RTFP) were estimated theoretically from (EFP) to experimental data of (V-?K) diagram to fatigue crack propagation. Temperature effect with (RTFP) was discussed. Crack velocity function denoted with stress intensity factor and temperature degrees has been determined to fatigue and creep crack propagation theoretically and comparative results this function with experimental data of (V-K or ?K) diagram .